On the existence of solutions of one-dimensional fourth-order equations - Shokooh, S.; Afrouzi , G. A.; Hadjian, A. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.9 Using variational methods and critical point theorems, we prove the existence of nontrivial solutions for one-dimensional fourth-order equations. Multiplicity results are also pointed out.